Gerontological design a study on residential environment and its influence on elderly subjective well-being - Lao, Eliah Fe C. (2023)
This study aimed to explore the influence of the residential environment, encompassing both physical and social aspects, further classified into physical and social domains, on the subjective well-being (SWB) among elderly individuals living in low-cost subdivisions. By utilizing the findings, the study developed guidelines that optimized residential communities and enhanced their potential as age-friendly environments. Data were collected from five subdivisions in General Santos City. The data gathered on perception across different domains of an age-friendly community and SWB were analyzed using mean scores. The results revealed a significant correlation of several domains of an age-friendly community (Housing, Outdoor Spaces and Buildings, Transportation, and Community Information) to elderly SWB. The existing conditions of subdivisions lack home repair and seasonal services, and home features for accessibility are of low quality. For outdoor spaces and buildings, prioritizing street maintenance, accessibility for pedestrians, and the maintenance of amenities is crucial. Regarding transportation, convenient access to public transportation services, terminals, and parking lots should be prioritized. Lastly, centralizing information sources and making them readily available in public places is essential for community information. Furthermore, interviews revealed that spatial organization and physical structure are significant factors for home modifications, while better street features, supervision, security, and provision of amenities were highlighted for community improvements. Based on these research findings, the study proposed architectural solutions that prioritize gerontological design principles to create age-friendly subdivisions. These solutions include high-quality housing, accessible facilities, well-designed transportation systems, well-maintained outdoor amenities, and social inclusivity. The study demonstrated the suitability of Lindenberg's SWB theory as a framework for examining the relationship between SWB and the residential environment. To enhance the study's comprehensiveness, the researcher recommends exploring additional factors that influence the SWB of older adults, by including diverse housing types in future studies.